Effects of strain rate during multi-directional forging on grain refinement and mechanical properties of AZ80Mg alloy - Miura, H.; Kobayashi, M.; Benjanarasuth, T. (My University, 2016)
Samples of AZ80Mg alloy were multi-directionally forged (MDFed) at various strain rates in the rage from 3.0× 10-3 s-1 to 3.0× 10-1 s-1 under decreasing temperature conditions. The MDFing pass temperatures employed were 653 K, 605 K and 553 K. These passes, each of 0.5 strain, were applied up to a cumulative strain of ΣΔϵ= 1.5 at maximum. The average grain size decreased with increasing cumulative strain and depended only weakly on the strain rate. Microstructures with average grain sizes of 0.84 μm, 0.88 μm and 1.2 μm were attained when MDFed at strain rates of 3.0× 10-1 s-1, 3.0× 10-2 s-1 and 3.0×10-3 s-1. The microstructure evolved at 3.0× 10-1 s-1 was less homogeneous. This difference is interpreted as being due to the higher stored energy causing static recrystallization in the latter MDFing condition. As a result, the best balance of the mechanical properties was attained by MDFing at 3.0× 10-2 s-1. In this case, ultimate tensile strength (UTS) of 445 MPa was achieved together with a fracture strain of 22%. By comparison, MDFing at 3.0× 10-1 s-1 led to lower UTS and ductility of 410 MPa and 15% while the yield stresses were comparable.
Keywords: AZ80 magnesium alloy; Mechanical properties; Multi-directional forging; Recrystallization; Ultrafine grains